Measures of Material Deprivation in OECD Countries - Boarini, Romina (OECD Social, Employment and Migration Working Papers, 2006)
The paper discusses the use of material deprivation measures for an analysis of poverty in OECD countries. Its main goal is to identify suitable survey questions that might be used in comparative analysis, as a first step towards the construction of more satisfactory poverty measures. The paper proposes a simple taxonomy of the broad notion of material deprivation into its objective and subjective dimensions and into its main components, and present data on the share of households reporting different types of material deprivation. It also proposes a simple summary measure of material deprivation, defined as the average of indicators across different items